2005
DOI: 10.1007/s10549-005-9110-y
|View full text |Cite
|
Sign up to set email alerts
|

Human gross cyst breast disease and cystic fluid: bio-molecular, morphological, and clinical studies

Abstract: For more than one and a half century the cystic disease of the breast has been recognized as the most frequent female benign breast lesion. Although some conundrums and controversies exist about the relation between gross cysts and breast cancer, recent evidence suggests that the multidisciplinary study of gross cystic breast disease (GCBD) may be a powerful tool for predicting the natural history of the multifaceted gross cyst pathology. A lot of papers have been published on breast cyst fluids (BCF) concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(94 citation statements)
references
References 177 publications
3
88
0
2
Order By: Relevance
“…Desde então, outros trabalhos foram surgindo com a evolução das técnicas moleculares e diversas proteínas foram sendo apontadas ao longo dos anos como sugestivas de biomarcadores para o câncer de mama, como exemplo, a prolactin inducible protein e a gross cystic disease fluid protein. 37 Nos últimos anos o NAF tem ganhado destaque novamente pela introdução da biópsia líquida e o avanço das tecnologias aplicadas à proteômica. A coleta do fluido, justamente por ser de baixo custo, tem despertado o interesse na clínica para investigação; porém, a coleta ainda é dolorosa e feita por meio de bombas a vácuo, que geram quantidades mínimas do fluido para pesquisa laboratorial.…”
Section: Salivaunclassified
“…Desde então, outros trabalhos foram surgindo com a evolução das técnicas moleculares e diversas proteínas foram sendo apontadas ao longo dos anos como sugestivas de biomarcadores para o câncer de mama, como exemplo, a prolactin inducible protein e a gross cystic disease fluid protein. 37 Nos últimos anos o NAF tem ganhado destaque novamente pela introdução da biópsia líquida e o avanço das tecnologias aplicadas à proteômica. A coleta do fluido, justamente por ser de baixo custo, tem despertado o interesse na clínica para investigação; porém, a coleta ainda é dolorosa e feita por meio de bombas a vácuo, que geram quantidades mínimas do fluido para pesquisa laboratorial.…”
Section: Salivaunclassified
“…[2] Several large studies have shown that the risk of breast cancer in women with GCBD to be 1.7 to 7.5 times higher, and women with an apocrine breast cyst may have a higher risk of developing breast cancer than women with breast cyst lined by flattened epithelium. [3][4][5] Histological risk factors for breast cancer have been also reported to be more common with type I cysts. [3] A variety of cancer bearing patients have been shown to have disturbances in carbohydrate, lipid and protein metabolisms.…”
Section: Introductionmentioning
confidence: 99%
“…These gross cyst types also differ in their natural history, particularly in terms of multiplicity and recurrence [11, 12]. Although care should be taken in translating the potential biological activity of several constituents (e.g., mitogenic growth factors, steroid hormones, proteolytic enzymes) into trophic effects within the breast and subsequent BC risk, gross cysts lined by apocrine epithelium show the ability to actively synthesize and secrete bioactive molecules [5], strengthening the epidemiological evidence of the increased risk for BC in GCBD-affected women [12].…”
mentioning
confidence: 99%
“…Most clinicians favor a policy of cautious/ close observation [20,21], even though there is no certain evidence that the risk for BC in GCBD will fall as a result. We are far from the certainty that biomolecular and morphological analyses of fluid that is needle aspirated from gross cysts will ever be an accurate predictor of BC risk [5], and more studies are needed to answer the question of whether GCBD (and/or associated hyperplastic lesions) increase the risk for BC and to stratify women with GCBD into high-risk groups for BC [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation